Tito Pravdan pilapiirroksissa 1949-1950 - Kangas Reeta (Finland, 2022)
The Image of Josip Tito in Pravda’s political cartoons
Following the split between the Soviet Union and Yugoslavia, Josip Broz Tito became the target of a Soviet propaganda campaign. The former ally was now portrayed as an enemy. This campaign also involved the use of political cartoons. The cartoons portrayed in a visual and easily comprehensible form the official Soviet view on matters. In this article, I examine the ways in which the political cartoons published in Pravda created an image of Tito as an enemy. In order to reposition Tito from being an ally to being an enemy, the cartoonists equated him with both contemporary (the USA and other market economy countries of the West) and past (Hitler's Germany) enemies. Simultaneously, they depicted Tito as a traitor who had abandoned the true Marxist-Leninist ideology for money.